Vitamin D evaluation based on demographics and calcium supplement intake in children suffering from acute febrile illness admitted in as tertiary care center - Badjate, Priyanka; Prasad, Brijendra (Indian Journal of Child Health, 2020)
Background: Vitamin D or sunshine vitamin is a vital steroid group of vitamins with its deficiency being common, especially among children. The literature establishing the correlation of dietary habits with Vitamin D levels in Indian population is scarce. Objective: This study aims to evaluate serum 25-hydroxyvitamin D (25(OH)D) level in the hospitalized children suffering from acute febrile illness (AFI) and find its correlation with calcium intake and demographic characters. Materials and Methods: The study was conducted at the pediatric department of a tertiary hospital of Maharashtra, over a period of 6 months in the children between the age groups of 1 month and 12 years, admitted with AFI and with or without clinical or biochemical evidence of rickets. After detailed history, evaluation of Vitamin D status was done in all children within 48 h of admission to the hospital using early morning sample of 2 ml of serum using chemiluminescent immunoassay method. We correlated Vitamin D levels with socioeconomic status (SES) along with various other parameters like serum calcium (S. calcium). Results: It was observed that with the improvement of SES, the Vitamin D deficiency (VDD) did not improve. The biochemical parameters such as S. calcium and alkaline phosphatase revealed a significant correlation with Vitamin D status. S. calcium level was significantly low in children with VDD. Radiological evidence of rickets was seen only in 40.5% of cases of VDD and 14.3% of cases of Vitamin D insufficiency and thus was not a diagnostic hallmark for rickets. Conclusion: The data suggested that VDD is very common among children aged 1 month–12 years and it is not correlated with SES and calcium intake. Efforts need to be made to improve the Vitamin D status by creating awareness among people.